(untitled) - Owen, Judith A. (New York, 2013)
The only textbook written for undergraduates by teachers of the course, this bestseller presents the most current concepts in an experimental context, conveying the excitement of scientific discovery, and highlighting important advances while providing unsurpassed pedagogical support for the first-time learner. The new edition is thoroughly updated, including most notably a new chapter on innate immunity, a capstone chapter on immune responses in time and space, and many new focus boxes drawing attention to exciting clinical, evolutionary, or experimental connections that help bring the material to life.
Sinh học miễn dịch
Keywords: Miễn dịch học,Immunology